Your skin and mine - Showers, Paul.; Kuchera, Kathleen (New York, NY : HarperCollins, 1991)
Explains the basic properties of skin, how it protects the body, and how it can vary in color.
2.8
K-3
Keywords: Skin -- Juvenile literature; Skin; Skin